R object-oriented programming : a practical guide to help you learn and understand the programming techniques necessary to exploit the full power R - Black, Kelly (Community experience distilled., 2014)
Chapter 5: Character and String Operations; Basic string operations; Six focused tasks; Determine the length of a string; Location of a substring; Extracting or changing a substring; Transform case; Splitting strings; Creating formatted strings; Regular expressions; Summary; Chapter 6: Converting and Defining Time Variables; Introduction and assumptions; Converting strings to time data types; Converting time data types to strings; Operations on time data types; Summary; Chapter 7: Basic Programming; Conditional execution; Loop constructs; for loops; while loops; repeat loops.